2021
DOI: 10.2147/prbm.s315760
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and Suicidal Behaviors in the Context of COVID-19 Pandemic in Bangladesh: A Systematic Review

Abstract: Background Without integration of the available information, appropriate suicide preventive actions can be hindered. Therefore, this study attempts to review the Bangladeshi COVID-19-related suicide studies for the first time. Methods For conducting a systematic review, the PRISMA guideline was adhered. Bangladeshi literatures concerning the COVID-19 pandemic related to either suicide case or suicidal behavior were identified within 1 to 10 April 2021, from the database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
88
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 72 publications
(98 citation statements)
references
References 37 publications
7
88
3
Order By: Relevance
“…In respect to gender-based insomnia suffering, female participants are reported at higher risk in this study, which is similar to the prior Bangladeshi studies conducted in the periods of normal [ 29 , 30 ] or pandemic [ 15 , 17 19 ]. Generally, females are highly prone to mental health suffering, a finding that is also consistent with the pandemic-related Bangladeshi studies [ 7 , 8 ]. In addition, the female gender is being reported to have higher knowledge and fear of COVID-19 [ 31 33 ], which can be the risk predictors of such a situation because other studies reported COVID-19 fear increasing sleep problems [ 18 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In respect to gender-based insomnia suffering, female participants are reported at higher risk in this study, which is similar to the prior Bangladeshi studies conducted in the periods of normal [ 29 , 30 ] or pandemic [ 15 , 17 19 ]. Generally, females are highly prone to mental health suffering, a finding that is also consistent with the pandemic-related Bangladeshi studies [ 7 , 8 ]. In addition, the female gender is being reported to have higher knowledge and fear of COVID-19 [ 31 33 ], which can be the risk predictors of such a situation because other studies reported COVID-19 fear increasing sleep problems [ 18 ].…”
Section: Discussionsupporting
confidence: 85%
“…There is enough evidence suggesting the impact of lockdown on economic conditions and mental wellbeing. Economic disruptions made by the pandemic is reported as the prominent suicide stressors in Bangladesh [ 7 ], which links to worsening mental health conditions, as suggested by the recent systematic reviews of the studies [ 7 , 8 ]. There are a number of studies on mental health issues like depression, anxiety, and stress; however, sleep problems are somewhat less studied in Bangladesh, although it is a major mental disorder [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, four major types of suicide stressors have been identified in the prior pandemics, whereas fear of being infected was regarded as the prominent suicide factor followed by social isolation, disruption of normal life, and burden of longterm illness (8,9). In the context of the COVID-19 pandemic, fear of COVID-19 infection is also reported as the main suicide mediating factor (1,7,10,11). Studies have identified various domains of fear related to the fear of COVID-19 infection, such as fear of oneself or their family members getting infected, fear of having economic losses and being unemployed, or fear of avoidance behaviors toward gaining knowledge about the pandemic or fear of making decisions on showing or not showing actions like whether to visit parents or not, whether to look for information on death rates or not, etc.…”
Section: Introductionmentioning
confidence: 99%
“…One study assessing the early effects of the COVID-19 pandemic in 21 high- and middle-income countries found that suicide rates were unchanged or even declined [ 45 ]. A systematic review looking at COVID-19-related suicide trends in Bangladesh found the prevalence of suicidal ideations to range between 5–19% and to increase as the pandemic progressed [ 46 ]. Another study found that the risk of COVID-19-related suicide increased within the first week of diagnosis, particularly during the acute phase while receiving treatment in a hospital [ 47 ].…”
Section: Discussionmentioning
confidence: 99%